THU0498 The Patients' Experience of Imaging: Views from a Group Convened to Support the Development of Points to Consider for the Use of Imaging in the Diagnosis and Management of Juvenile Idiopathic Arthritis. (9th June 2015) - Colebatch-Bourn, A.N.; Malattia, C.; Collado, P.; D'Agostino, M.A.; Hemke, R.; Jousse-Joulin, S.; Maas, M.; Martini, A.; Naredo, E.; Østergaard, M.; Rooney, M.; Tzaribachev, N.; et al.
Abstract : Objectives: To explore patients' perspectives on the use of imaging to support development of points to consider for the use of imaging in the diagnosis and management of juvenile idiopathic arthritis (JIA) in clinical practice.[1] Methods: A task force has recently produced points to consider (PTC) for the use of imaging in the diagnosis and management of JIA in clinical practice. Given the challenges of asking children or young adults to attend consensus meetings with the task force members, a separate Patient and Public Involvement (PPI) event was arranged following the second task force meeting where the process and results were presented and all comments were recorded. The PPI event was attended by one child and two young adults with a diagnosis of JIA, two parents of children with JIA, two consultant rheumatologists, one with a special interest in paediatric rheumatology, a paediatric rheumatology nurse specialist and a paediatric research senior nurse. During thorough round table discussion thoughts and ideas related to a child's experience of imaging for JIA were generated. Results: There were extensive discussions around differences in the experience of imaging for children with JIA. Although the patients involved were young adults they had personal experience of JIA and also of imaging from early childhood (4 years old in one case). One had experienced conventional X-ray radiology (CR) and the other two had experienced CR, ultrasound (US) and magnetic resonance imaging (MRI). The PPI representatives gave no specific comments on the PTC as they felt they were directed towards medical staff but "thought they all sounded reasonable" and had no objections. However, they did make a number of overarching observations related to imaging in general, and on the individual imaging modalities (table ). Conclusions: This process has provided invaluable insight into understanding the patient perspective on various aspects of imaging in JIA. It highlights the importance of involving patients as far as possible in the development of clinical recommendations. In particular, key concerns related to the environment in which the imaging takes place, the ease of positioning and time taken, the importance of understanding the technology and having rapid access to a result. References: Colebatch-Bourn AN, et al. EULAR-PRES points to consider for the use of imaging in the diagnosis and management of juvenile idiopathic arthritis in clinical practice. Unpublished data, 2015. Disclosure of Interest: None declared